The Influence of Talking Stick Learning Model on Pancasila Education Learning Outcomes of Grade IV Students at UPTD SD Negeri 122371 Pematangsiantar - Lumbantoruan, Hotnida; Sianturi, Canni Loren; Siahaan, Theresia Monika (EDUCTUM: Journal Research, 2025)
This study aims to determine: The Effect of Talking Stick Learning Model on the Learning Outcomes of Pancasila Education of Grade IV Students of UPTD SD NEGERI 122371 Pematangsiantar. The type of research used in this study is quantitative research. The research design that will be used is experimental, with the form of Pre-Experimental Design with "one group pretest posttest design". The sample in this study were grade IV students at UPTD SD Negeri 122371 Pematangsiantar totaling 25 students, where 11 were male and 14 were female. The instrument used in this study was in the form of multiple-choice questions. Hypothesis testing shows that there is a significant influence on this study from the data that has been tested, the data can be seen from the data analysis obtained the average results of the pretest (53.76) and posttest (81.28). Based on the results of the study, it can be concluded that there is an Influence of the Talking Stick Learning Model on the Learning Outcomes of Pancasila Education for Grade IV Students of UPTD SD NEGERI 122371 Pematangsiantar, this is proven by the results of the hypothesis test showing that t count is more than t table (16.372> 1.711). This fact shows that the t count obtained is very significant. Thus it is concluded that there is an influence of the Talking Stick learning model on the learning outcomes of Pancasila Education for grade IV students of UPTD SD NEGERI 122371 Pematangsiantar